2020
DOI: 10.20944/preprints202007.0169.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Macroplastic Storage and Remobilization in Rivers

Abstract: The paper presents a conceptual model of the route of macroplastic debris (5 > mm) through a fluvial system, which can support future works on the overlooked processes of macroplastic storage and remobilization in rivers. We divided the macroplastic route into (1) input, (2) transport (3) storage, (4) remobilization and (5) output phases. Phase 1 is mainly controlled by humans, phases 2–4 by fluvial processes, and phase 5 by both types of controls. We hypothesize that natural character… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…the trapping of macroplastic debris by riverine vegetation will be greater (and thus mean travel distances shorter) during the growing season (when vegetation density and cover are greater and vegetation structure is more complex; see Section 1.6.3). Liro et al (2020) suggest that the change in vegetation roughness caused by a seasonal change in vegetation characteristics and floristic composition favours plastic storage. Therefore, during the during the growing season, macroplastic debris is more likely to be trapped, relative to the non-growing season.…”
Section: Limitationsmentioning
confidence: 98%
“…the trapping of macroplastic debris by riverine vegetation will be greater (and thus mean travel distances shorter) during the growing season (when vegetation density and cover are greater and vegetation structure is more complex; see Section 1.6.3). Liro et al (2020) suggest that the change in vegetation roughness caused by a seasonal change in vegetation characteristics and floristic composition favours plastic storage. Therefore, during the during the growing season, macroplastic debris is more likely to be trapped, relative to the non-growing season.…”
Section: Limitationsmentioning
confidence: 98%
“…During transportation, plastic interacts mechanically with water and river sediments, causing the particles to become mechanically fragmented [13]. When macroplastics are deposited for a long time, macroplastics will undergo biochemical degradation [14]. Any physical or chemical change in the polymer is caused by environmental factors, such as light, heat, humidity, chemical conditions or biological activity [15].…”
Section: % Compositionmentioning
confidence: 99%
“…The high level of beaching in the composite simulation (Figure 4) and the sensitivity of model results to the three shoreline interaction options (Figure 8) suggest that the lack of beached particle remobilization (Liro et al, 2020) in the model is one of the most important limitations associated with particle transport. Indeed, Jalón-Rojas et al (2019) found their model results to be sensitive to the main remobilization parameter (there referred to as "washingoff "), which is the particle half-life on land.…”
Section: Model Limitationsmentioning
confidence: 99%